1965
DOI: 10.1042/bj0970449
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene production from methionine

Abstract: 1. A new reaction is described in which ethylene is formed from the Cu+-catalysed breakdown of methionine in phosphate buffer at 300 in air. Some of the other products of the reaction are methionine sulphone, methionine sulphoxide, homocysteic acid, homocystine, acrolein, dimethyl disulphide, methanethiol, ethyl methyl sulphide, methane and ethane. These are considered to be produced in different reaction pathways. The formation of ethylene in a model system in which Cu+ catalyses the breakdown of peroxidated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
65
0

Year Published

1966
1966
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(68 citation statements)
references
References 6 publications
3
65
0
Order By: Relevance
“…Yang (30) speculated that the pea system may be a peroxidase and later Mapson and Wardale (24) further characterized the cauliflower enzyme system and concluded that the enzyme may indeed be a peroxidase. Although methionine appears to be a substrate for the production of ethylene in pea tissue treated with IAA (8,22), peroxidase only produces ethylene from methional or a-keto-y-methylthiobutyric acid (21), but not from S-adenosyl methionine or methionine. Furthermore, there is evidence that methional and the a-keto-analogue are not converted to ethylene as readily as methionine in vivo, and in addition C-2 of methionine is not converted to CO, in vivo (8), whereas peroxidase converts C-2 of the a-ketoanalogue to COa in vitro (31).…”
Section: Discussionmentioning
confidence: 99%
“…Yang (30) speculated that the pea system may be a peroxidase and later Mapson and Wardale (24) further characterized the cauliflower enzyme system and concluded that the enzyme may indeed be a peroxidase. Although methionine appears to be a substrate for the production of ethylene in pea tissue treated with IAA (8,22), peroxidase only produces ethylene from methional or a-keto-y-methylthiobutyric acid (21), but not from S-adenosyl methionine or methionine. Furthermore, there is evidence that methional and the a-keto-analogue are not converted to ethylene as readily as methionine in vivo, and in addition C-2 of methionine is not converted to CO, in vivo (8), whereas peroxidase converts C-2 of the a-ketoanalogue to COa in vitro (31).…”
Section: Discussionmentioning
confidence: 99%
“…The first utilizes linlolenate as substrate (1) and the second requires methionine, ethioninie, or the a-hydroxy analogue of imethionine as substrate (2). Both …”
mentioning
confidence: 99%
“…The conversion of methionine to etlhylene in model systems (8,19) and in plant tissues (2,9) has been demonstrated. In the FMN-light mediated model system (19), it has been established that methionine is converted to ethylene via methional (,a-methylthiopropionaldehyde) as an intermediate.…”
mentioning
confidence: 99%